2016
DOI: 10.1115/1.4034808
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Workflow for Production Allocation During Water Flooding

Abstract: This paper presents an efficient production optimization scheme for an oil reservoir undergoing water injection by optimizing the production rate for each well. In this approach, an adaptive version of simulated annealing (ASA) is used in two steps. The optimization variables updating in the first stage is associated with a coarse grid model. In the second step, the fine grid model is used to provide more details in final solution search. The proposed method is formulated as a constrained optimization problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Moreover, an adaptive simulated annealing algorithm was employed by Azamipour et al, for the production optimization of a field undergoing water injection: therein, optimization time reduction was attained by sequentially implementing coarse and fine grids without discernible loss in model accuracy. 33 The authors improved their optimization approach in a subsequent article, using a hybrid genetic algorithm. 34 As part of their improvements, streamline simulation has also been adopted for the determination of good initial guesses for the water injection rates.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an adaptive simulated annealing algorithm was employed by Azamipour et al, for the production optimization of a field undergoing water injection: therein, optimization time reduction was attained by sequentially implementing coarse and fine grids without discernible loss in model accuracy. 33 The authors improved their optimization approach in a subsequent article, using a hybrid genetic algorithm. 34 As part of their improvements, streamline simulation has also been adopted for the determination of good initial guesses for the water injection rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A complex economic objective function with business considerations has been adopted therein toward enhancing planning decisions over a field's lifetime. Moreover, an adaptive simulated annealing algorithm was employed by Azamipour et al, for the production optimization of a field undergoing water injection: therein, optimization time reduction was attained by sequentially implementing coarse and fine grids without discernible loss in model accuracy . The authors improved their optimization approach in a subsequent article, using a hybrid genetic algorithm .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unlike single processing services with limited capabilities, geospatial service chains implement multiple functions to meet users' needs. Users frequently composite multiple services into a service chain based on the relationship between services, commonly employed in the fields of hydrology [1][2][3][4] and the environment [5,6], resulting in value-added service [7].…”
Section: Introductionmentioning
confidence: 99%
“…What's more, researchers also used NMR methods to quantitatively study the residual oil distribution and pore size distribution using different NMR T2 spectrums [7][8][9][10]. Research has shown that porous systems containing remaining oil are significantly influenced by the pore scale entrapment characteristics of the oil phase [11,12].…”
Section: Introductionmentioning
confidence: 99%